"We are never taught anything about the elderly." Establishing the gap in elderly health care competencies in nursing education in Uganda - Faith Nawagi; John Mukisa; Josephine Nambi Najjuma; Rose C. Nabirye (BMC, 2022)
Abstract Background Nurses contribute the largest portion of Uganda's health workforce providing care to individuals of all ages and communities. However, despite the growing number of the elderly population in Uganda with improved life expectancy, there is hardly any study that has looked at the elderly health care competencies in the nursing training programs at various levels. This paper provides an overview of the gaps in elderly health care competencies in nursing education in Uganda. Methods We conducted a descriptive qualitative cross-sectional study that involved document review, Key Informant Interviews (KIIs) with nursing leaders, and Focus Group Discussions ( FGDs) with faculty at all levels of nursing training and nurses in practice. Data was analyzed using latent and manifest content analysis with Open Code software 4.03. Common categories were identified and incorporated into a matrix to create themes. Results Almost all the curricula and minimum standards for training nurses at certificate, diploma, and degree levels lack a module and nursing competencies on elderly nursing care. This is aggravated by a lack of faculty trained in elderly health care skills, and a lack of specialized wards for nursing elderly care clinical training among others. Conclusions There is hardly any elderly health care training module and elderly nursing competencies at all levels of nursing training in Uganda.